Learning to Read and Write the Qur'an in the New Normal Era in Junior High School: Pembelajaran Baca Tulis Al-Qur’an dalam Era New Normal di Sekolah Menengah Pertama - Miranda Puspayadi; Imam Fauzi (Universitas Muhammadiyah Sidoarjo, 2021)
Learning to Read and Write Al-Quran is an effort to improve individual attitudes/behaviors by prioritizing the formation of noble character and achievement. The objectives of this study are: 1) To find out more about the Al-Qur'an Reading and Writing Learning in the new normal era at Al-Islam Krian Junior High School. 2) To find out more about the analysis of the achievement of learning to read and write the Qur'an in the new normal era at Al-Islam Krian Middle School. The method used is descriptive qualitative method using the method of observation, interviews and documentation. The analysis technique used in this research is data reduction, data presentation and conclusion drawing. The results obtained are: 1) Learning to Read and Write the Qur'an in the New Normal Era at SMP Al-Islam Krian, 2) The achievement of learning to read and write the Qur'an.